Dysphagia after Cardiac Operations is Associated with Increased Length of Stay and Costs. Issue 10 (October 2016) - Nguyen, Son; Zhu, Allen; Toppen, William; Ashfaq, Adeel; Davis, Jessica; Shemin, Richard; Mendelsohn, Abie H.; Benharash, Peyman
Although the true incidence of postoperative dysphagia after cardiac surgery is unknown, it has been reported to occur in 3 to 21.6 per cent of patients. Historically, dysphagia has been associated with increased surgical complications and prolonged hospital stay. This study aimed to evaluate the costs and outcomes associated with dysphagia after cardiac surgery. Patients undergoing nonemergent, nontransplant cardiac operations between June 2013 and June 2014 were eligible for inclusion. Independent predictors of cost were identified through a multivariate linear regression model. Of the 354 patients (35% female) included for analysis, 56 (16%) were diagnosed with postoperative dysphagia. On univariate analysis, patients with dysphagia had increased intensive care unit and total hospital lengths of stay (11.8 vs 5.2 days, P < 0.001 and 18.2 vs 9.7 days, P < 0.001, respectively), and a 57 ± 15 per cent increase in cost of care ( P < 0.001). Dysphagia was not associated with higher rates of in-hospital mortality (3.6% vs 3.0%, P = 0.83). On multivariate linear regression, the development of dysphagia was independently associated with a 45.1 per cent increase in total hospital costs [95% confidence interval (31% and 59%), P < 0.001]. Dysphagia is an independent and major contributor to health care costs after cardiac operations, suggesting that postoperative dysphagia represents a highly suitable target for quality improvement and cost containment efforts.